INNOVATION OF THE LABOR MARKET IN THE CONTEXT OF SOCIAL CHALLENGES AS A COMPONENT OF ENSURING SUSTAINABLE DEVELOPMENT OF UKRAINE - Зелінська, Галина Олексіївна (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2020)
Abstract. The article deals with the challenges that accompany the Ukrainian labor market today. An innovative model of economic development is able to accelerate Ukraine’s progress towards sustainable development. The research proves that the main factor of structural changes in the Ukrainian labor market is the innovative nature of the development of economic sectors. The cyclical nature of the development of the labor market structure under the influence of innovative processes in the national economy is analyzed. It has been found out that the dynamics of state support of innovative activity of enterprises of the national economy sectors causes transformational changes in the labor market, namely facilitates the modernization of jobs, leads to complication of production processes and places special requirements on the professional competencies of employees. Since social development is one of the components of sustainable development, human resources issues need special attention. Changing demand in the labor market in different sectors of the economy is driven by innovative changes, and the latter require the accumulation of new knowledge, which places particular demands on the competences and skills of the workforce. It is noted that the sustained economic growth today is largely provided not by agriculture and industry, but by the IT sphere. Attention is drawn to the fact that the developed countries of the world devote a considerable amount of money to innovation and new technologies. In Ukraine, scientific research at enterprises is conducted much less due to insufficient funding for research, which does not allow the state to move towards sustainable economic development. Demand in the labor market is shifting from the traditional economy, driven by innovative shifts. It is determined that in the Ukrainian economy the intensity of structural shifts in demand in the labor market are influenced by the rising and falling waves of the macroeconomic cycle, which is accompanied by the formation of a structure of the economy of a qualitatively new type. In the downward wave of the macroeconomic cycle, the demand structure in the labor market is the least stable compared to the other phase of the macroeconomic cycle. It has been found that, on the one hand, the change and development of public and individual needs in the economic system leads to diversification of economic interests of economic entities in the investment sphere, forming the preconditions for structural changes in the labor market. On the other hand, structural changes in the labor market are shaped by profound and complex changes in the socio-economic system, which is reflected at the macro level as the national economy moves from one development trajectory to another. It is determined that the implementation of an innovative model for sustainable development of Ukraine and the labor market depends directly on the educational level of citizens and the ability of economic entities to generate innovative activity. It is the field of education that can change the mass consciousness of people, focusing them on the preservation of natural and cultural values, ethical, humane attitude to life, finding a compromise where the economic interests of production conflict with the environmental interests of society.